The new species of Pupilla Turton, 1831 genus (Mollusca, Pulmonata) from the upper cenozoic deposits in Kazakhstan and adjacent areas - Prysiazhniuk, V.A. (Reports of the National Academy of Sciences of Ukraine, 2017)
The new species, which is specific to the Eopleistocene of the Altai and adjacent areas, such as Pupilla tschumakovi and Pupilla almuhambetovae from the Upper Miocene of the Tian Shan, as well as the nev subspecies Pupilla tschumakovi altaica, are described. Pupilla poltavica O. Boettger, 1889 is a separate species typical of the Pleistocene and Eopleistocene in Eastern Europe and Asia.